Pengembangan Aplikasi Order Foto Berbasis Web untuk Meningkatkan Layanan Konsumen di CV Bina Anak Papua - Marco Yeri Maswatu; Gunawan Prayitno (Jurnal Teknologi dan Informatika, 2024)
The involvement of the community in the development of a web-based photo ordering application using the waterfall method aims to improve customer service during the online photo ordering process. The background of this community service is based on the difficulties faced by the public in practically ordering photos. The main goal of this community service is to develop an application that simplifies the ordering process. The development method used is the waterfall method, which includes analysis, system design, implementation, testing, and maintenance. The results of this application development include the results of each development stage with the waterfall method, implementation results, and the main conclusion of this community service.